Atomic layer deposition for membrane interface engineering. Issue 44 (6th November 2018) - Yang, Hao-Cheng; Waldman, Ruben Z.; Chen, Zhaowei; Darling, Seth B.
Abstract : Atomic layer deposition represents a burgeoning and appealing technique for membrane interface engineering. Abstract : In many applications, interfaces govern the performance of membranes. Structure, chemistry, electrostatics, and other properties of interfaces can dominate the selectivity, flux, fouling resistance, and other critical aspects of membrane functionality. Control over membrane interfacial properties, therefore, is a powerful means of tailoring performance. In this Minireview, we discuss the application of atomic layer deposition (ALD) and related techniques in the design of novel membrane interfaces. We discuss recent literature in which ALD is used to (1) modify the surface chemistry and interfacial properties of membranes, (2) tailor the pore sizes and separation characteristics of membranes, and (3) enable novel advanced functional membranes.